La jurisprudencia constitucional colombiana en los conflictos vida-libertad (2006)
This advance report constitutes a brief summary of the research project claims currently developed by Professor Claudia Helena Forero for her doctoral dissertation in Law. The investigation seeks to identify if, from the new juridical rationale –which is the practical rationale— there is the possibility of harmonizing the right to life and the rights to freedom without harming any of them, when bearers of these fundamental rights look for waiving or delaying one right to grant priority to the other. This advance report was presented in the First Journey of Research Results Socialization, held at the University of La Sabana on May 11 and 12 of 2006 and the lecture was granted a “Special Mention”.